2012
DOI: 10.1080/02786826.2012.692492
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metal Distribution in PM10During Asian Dust and Local Pollution Events Using Laser Induced Breakdown Spectroscopy (LIBS)

Abstract: Hourly concentrations of heavy metals in PM 10 samples were continuously measured using Laser Induced Breakdown Spectroscopy (LIBS) to determine the metal distribution among Asian Dust (AD) events, local pollution events, and nonevents. Quantification of metals was performed by establishing a calibration line between 24 h average data determined by the ICP-MS after filter sampling and LIBS intensity data. It was found that in AD and local pollution events, significant anthropogenic heavy metals, such as Pb, Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The progress in this large field was reviewed by Hahn [52] a few years ago. Some noteworthy results of environmental LIBS aerosol analysis include development of methods for more efficient particle collection on a substrate [53], differentiation between gas-phase and particulate analytes [160], and a correlation study of heavy-metal concentrations in Asian dust and local pollution events [161].…”
Section: Environmental and Geological Applicationsmentioning
confidence: 99%
“…The progress in this large field was reviewed by Hahn [52] a few years ago. Some noteworthy results of environmental LIBS aerosol analysis include development of methods for more efficient particle collection on a substrate [53], differentiation between gas-phase and particulate analytes [160], and a correlation study of heavy-metal concentrations in Asian dust and local pollution events [161].…”
Section: Environmental and Geological Applicationsmentioning
confidence: 99%
“…Kwak et al developed a LIBS experimental system with a particle collection substrate stage that could automatically move in a specific time interval. 51 The detection results of the PM in every time interval were averaged to obtain time-resolved compositional information about the PM. Zhang et al carried out research on the qualitative and quantitative detection of heavy metal elements in PM samples.…”
Section: Case Studiesmentioning
confidence: 99%
“…Initial studies, using lter samples spiked with reference silica, kaolin and coal dust samples, and by undertaking measurements at the Si 288.16 nm emission line, suggested that this approach had potential as an end-of-shi screening tool. In the hourly monitoring 36 of metals (e.g., Al, Ca, Cr, Fe, Pb and Zn) in PM 10 particles during Asian dust pollution episodes, the particles were sampled through a PM 10 size-selective inlet, dried and focused as a spot onto a movable nylon lter. By moving a sample spot under a Nd:YAG laser it could be interrogated for their elemental composition.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Aer heating at 1450 C for 20 min, the blanks of 3.7 Â 10 À21 mole for 3 He and 1.1 Â 10 À15 mole for 4 He were an order of magnitude better than those of a conventional double vacuum furnace. Large accelerators are normally necessary to separate 36 Cl from its stable isobar 36 S but these measurements can now be performed with modern 5 MeV AMS instruments using gas stripping to produce the highest quality beams. A protocol 325 for the accurate determination of 36 Cl included ID for stable Cl measurement and separation from 36 S on a relatively small automated spectrometer using 30 MeV ions.…”
Section: Instrumental Analysismentioning
confidence: 99%